National minimum wage implementation in Malaysia - Wee Yu Ghee; Mohd Rosli Mohamad; Noraani Mustapha; Sharan Kaur (2014)
Malaysia had introduced the Minimum Wage Policy in May 2012 and employers were given until July 2013 to begin complying with the new regulation. The policy mandates a floor wage of RM900 (equivalent to USD300) and RM800 (equivalent to USD267) permonth for Peninsular and East Malaysia respectively. While many low income employees, especially unskilled workers, were overjoyed by the gazetted Minimun Wage Order, such move has outraged small and medium enterprises (SMEs) which are reluctant to comply due to possible increase in operational costs and even close-downs. This paper seeks to gather the level of awareness and perception of SME's towards this policy, their rate of compliance and outcomes as reported by the SMEs. Data was collected from 459 small and medium enterprises in Malaysia. Findings show that SMEs which are complaint have high level of awareness and have positive perceptions towards minimun wage order. However, level of awareness and perception are not significantly related to non-compliance. Some other negative effects reported include unemployment, foreign workers employment, increase in business costs, hike in inflation, effect on foreign direct investments and many more. SMEs also question the rationale for single minimun wage order whilst other neighboring countries resorted to multiple wage according to sector or region. The findings from this research which structure the vies and feedback accordingly by region, state, industry and sectors will be usefull not only to all SMEs but also to the National Wage Consultative Council and the Ministry of Human Resources